Istiqlal Mosque: Bridging Tradition, Modernity, and Muslim Societies - Alam, Lukis; Fanani, Fahril (Matan : Journal of Islam and Muslim Society, 2025)
This study examines the integration of tradition and modernity in Muslim societies through the lens of the Istiqlal Mosque, the largest mosque in Indonesia, located in Jakarta. As a symbol of national pride, Islamic identity, and communal unity, the mosque represents a unique blend of architectural heritage, contemporary design principles, and the social dynamics of Muslim communities. The research employs qualitative methods, analyzing the mosque's architectural elements, design philosophy, and functional aspects to investigate how traditional Islamic values harmoniously coexist with modern technological advancements. Through a comprehensive review of design documents and site observations, the study highlights the mosque's role as a reflection of Indonesia's diverse cultural and religious landscape and a space that nurtures the collective identity and practices of Muslim communities. The findings reveal that the Istiqlal Mosque is a model for merging historical traditions with modern innovations and societal needs.